Expression of KID syndromic mutation Cx26S17F produces hyperactive hemichannels in supporting cells of the organ of Corti - Abbott, Ana C.; García, Isaac E.; Villanelo, Felipe; Flores-Muñoz, Carolina; Ceriani, Ricardo; Maripillán, Jaime; Novoa-Molina, Joel; Figueroa-Cares, Cindel; Pérez-Acle, Tomas; Sáez, Juan C.; Sánchez, Helmuth A.; Martínez, Agustín D. (Frontiers in Cell and Developmental Biology, 2023)
Some mutations in gap junction (GJ) protein Connexin 26 (Cx26) lead to syndromic deafness, where hearing impairment is associated with skin disease, like in Keratitis Ichthyosis Deafness (KID) syndrome. This condition has been linked to hyperactivity of connexin hemichannels (HCs) but this has never been demonstrated in cochlear tissue. Moreover, some KID mutants, like Cx26S17F, form hyperactive HCs only when co-expressed with other wild type connexins. In this work we evaluated the functional consequences of expression of a KID syndromic mutation, Cx26S17F, in transgenic mouse cochlea, and whether co-expression of Cx26S17F with Cx30, another Cx expressed in cochlea, leads to the formation of hyperactive HCs. Indeed, we found that cochlear explants from constitutive knock in Cx26S17F mice or by conditional in vitro cochlear expression of Cx26S17F produce hyperactive HCs in supporting cells of the organ of Corti that are insensitive to most common HCs blockers. These conditions also produce loss of hair cells stereocilia and degeneration of the organ of Corti, which is already observable after 24 hours of mutant expression. In supporting cells we found high co-localization between Cx30 and Cx26S17F. Therefore, the functional properties of HCs formed in cells co-expressing Cx26S17F and Cx30 were studied in oocytes and HeLa cells. Cx26S17F did not form functional HCs and GJC, but cells co-expressing Cx26S17F with Cx30 present hyperactive HCs insensitive to HCs blockers, Ca+2 and La3+, resulting in more Ca2+ influx and cellular damage. Molecular dynamic analysis of a putative heteromeric HC formed by Cx26S17F and Cx30 present alterations in extracellular Ca2+ binding sites that control channel gating. These results support that in KID syndrome hyperactive HCs are formed by interaction between Cx30 and Cx27S17F in supporting cells causing damage of hair cells and deafness in KID syndrome.